Las narrativas autobiográficas en la construcción de la experiencia y el sí mismo - González, María Fernanda (2018)
The article offers a semiotic and psychogenetic explanation of how autobiographical narratives organize experiences and give a sense of continuity to the self. Narratives are communicative actions that are articulated in two complementary directions. On the one hand they participate in the interpretation and construction of meanings about a situation and on the other they give meaning to their own performance. From this point of view, we can understand how the narrative identity is constructed - in a mediated and dialogical way- which leads to the ethical and aesthetic appreciation of the own performances and of the self.